Cervical Cancer Incidence Correlation With Hormonal Contraceptive Use : Cervical Cancer Incidence Correlation With Hormonal Contraceptive Use - nur zuwariah; Rizki Amalia; Syafaatul Ainiyah (Jurnal Ilmiah Kesehatan, 2021)
One of the most dangerous diseases for Indonesian women is cervical cancer. Hormonal contraceptive use is one of the risk factors for cervical cancer, especially in prolonged use for more than five years. This study evaluates the correlation between hormonal contraceptive use with cervical cancer incidence in Surabaya Wisnuwardhana Cancer Foundation. In this research, the authors used the analytical design with the cross-sectional approach. There were 30 respondents selected with the purposive sampling technique. The independent variable was hormonal contraceptive use, and the dependent variable was cervical cancer incidence. The instruments utilized questionnaires and medical records. Data analysis applied the Rank-spearman test with the significance level of α = 0.05. The results showed that most of the respondents (63,3%) used hormonal contraception. Almost half of them (46.7%) are categorized in class 2 of pap smear classification (mild infection). Hormonal contraceptive use correlated with cervical cancer incidence (p=0.005). The prolonged hormonal contraceptive use, the greater cervical cancer incidence in women.